Histone acetylation in refractory sudden sensorineural hearing loss patients after intratympanic methylprednisolone perfusion. Issue 10 (11th September 2019) - Xie, L; Hou, J; Qi, H; Dai, Y; She, W
Abstract: Objective: To examine the relationship between the therapeutic effect of intratympanic methylprednisolone perfusion and histone acetylation in refractory sudden sensorineural hearing loss. Methods: Thirty-four refractory sudden sensorineural hearing loss patients were enrolled and treated with intratympanic methylprednisolone perfusion. Pure tone average, acetylated histone H3, acetylated histone H4 and histone deacetylase 2 (HDAC2) were measured in peripheral blood mononuclear cells before and after intratympanic methylprednisolone perfusion. Sixteen healthy volunteers were recruited to obtain normal reference values. Results: Pure tone average in sudden sensorineural hearing loss patients improved from 84.14 ± 13.54 dB to 73.56 ± 18.45 dB after intratympanic methylprednisolone perfusion. Up-regulations in HDAC2 protein level, and down-regulations in histone H3 and H4 acetylation were observed in the intratympanic methylprednisolone perfusion sensitive group (pure tone average gain of 15 dB or more), while no significant changes were observed in the intratympanic methylprednisolone perfusion insensitive group (pure tone average gain of less than 15 dB). Conclusion: Intratympanic methylprednisolone perfusion can improve hearing in a considerable number of refractory sudden sensorineural hearing loss patients. The therapeutic effect is closely related to reduced histone acetylation.